Паліноіндикація атмосферного повітря м. Чернівці - Sytnikova, Iryna; Филипчук, Тетяна (My University, 2019)
Проведена моніторингова оцінка рівня техногенної трансформації середовища за життєздатністю пилку Malus domestica Borkh. і Prunus cerasus L. Показано, що у відповідь на підвищення рівня техногенного навантаження у біоіндикаторів зростала частка стерильного пилку. Виявлена більша чутливість M. domestica, ніж P. cerasus за рахунок збільшення частки пилку з середнім вмістом крохмалю у відповідь на атмосферне забруднення. Зазначена особливість розширює можливості її застосування в якості біоіндикатора та може свідчити про певний рівень техногенної трансформації довкілля. За інтегральним умовним показником ушкодженості біоіндикаторів встановлено «задовільний» екологічний стан на вулицях Небесної Сотні, 18- А; Ф. Полєтаєва, 3; П. Орлика, 1; Салтикова-Щедрина, 29; Руська, 178 та Небесної Сотні, 10-В, тоді як в усіх інших моніторингових точках екологічна ситуація – «еталонна». Основна причина підвищення стерильності пилку біоіндикаторів на вказаних вулицях – близьке розташування з усіх боків автодоріг з активним рухом автотранспорту та затори на них.
PALYNOINDICATION OF ATMOSPHERIC AIR IN CHERNIVTSI CITY
The monitoring evaluation of anthropogenic transformation level of the environment was made according to viability of pollen Malus domestica Borkh. and Prunus cerasus L. The research was conducted in 2015-2017. The monitoring areas were located on the territories of preschool- and general educational institutions of Chernivtsi city. The pollen of the plants, which grow in locations of the background territory (landscape wildlife preserve Tsetsyno), was used as a control. As the result of the research, it was found out that the increase of anthropogenic loading level caused the productivity rise of sterile pollen grain. It was also discovered that M. domestica has a higher sensitivity than P. cerasus due to its capacity to produce fertile pollen with mean concentration of starch as a response to the atmospheric pollution. The mentioned feature of M. domestica expands the opportunities of its use as a bioindicator and also can indicate the anthropogenic transformation of environment. According to the integral conditional index of bioindicator’s damage, it was assessed that a satisfactory state of environment is on the Nebesnoi Sotni 18-A st., F. Poletaeva 3 st., Saltykova-Shedrina 29 st., Ruska 178 st. and Nebesnoi Sotni 10-B st., when an ecological situation in other monitoring areas corresponds to the standards of cleanness. The main reason for the increase of pollen sterility of the bioindicators on the above-listed streets is a close proximity to the highways with an active traffic and traffic congestion.
Keywords: моніторинг; урбоекосистема; паліноіндикація; життєздатність пилку; пилок із високим і середнім вмістом крохмалю; стерильний пилок; Malus domestica Borkh.; Prunus cerasus L.